Systematic reappraisal of marsh-orchids native to Scotland - Richard M. Bateman; Ian Denholm; Lindsey McLeod; William Craig; Richard A. Ennos (Kew Bulletin, 2023)
Summary The intensively studied Eurasian orchid genus Dactylorhiza has become a model system for exploring allopolyploid evolution, yet determining the optimal circumscriptions of, and most appropriate ranks for, its constituent taxa remain highly controversial topics. Here, novel allozyme data and detailed morphometric data for 16 Scottish marsh-orchid populations are interpreted in the context of recent DNA sequencing studies. Despite being derived from the same pair of parental species, the two allopolyploid species that currently occur in Scotland can reliably be distinguished using allozymes, haplotypes, ribotypes or sequences of nuclear genes. A modest range of diverse morphological characters are shown to distinguish the two molecularly-circumscribed species, but they have in the past been obscured by equivalent levels of infraspecific variation in characters rooted in anthocyanin pigments; these characters are better employed for distinguishing infraspecific taxa. Dactylorhiza francis-drucei (formerly D. traunsteinerioides ) is confirmed as being distinct from the continental D. traunsteineri/lapponica , probably originating through allopatric isolation once the continental lineage reached Britain. All Scottish populations are attributed to the comparatively small-flowered, anthocyanin-rich subsp. francis-drucei , which includes as a variety the former D. 'ebudensis' ; the less anthocyanin-rich subsp. traunsteinerioides is confined to Ireland, North Wales and northern England. In contrast with D. francis-drucei , only a minority of Scottish populations of D. purpurella are attributed to the anthocyanin-rich race, var. cambrensis . This species most likely originated through an allopolyploidy event that occurred comparatively recently within the British Isles, as it contains allozyme alleles distinctive of British rather than continental D. incarnata (its diploid pollen-parent). In contrast, the rare Scottish population of D. incarnata subsp. cruenta shares with its Irish counterparts a continental genotype, and is most likely a recent arrival in Scotland through long-distance dispersal. Among all European allotetraploid dactylorchids, D. purpurella is the species that most closely resembles D. incarnata , both molecularly and morphologically.

Mitigation translocation as a management tool - Holly S. Bradley; Sean Tomlinson; Michael D. Craig; Adam T. Cross; Philip W. Bateman (Conservation Biology, 2022)
Mitigation translocation is a subgroup of conservation translocation, categorized by a crisis‐responsive time frame and the immediate goal of relocating individuals threatened with death. However, the relative successes of conservation translocations with longer time frames and broader metapopulation‐ and ecosystem‐level considerations have been used to justify the continued implementation of mitigation translocations without adequate post hoc monitoring to confirm their effectiveness as a conservation tool. Mitigation translocations now outnumber other conservation translocations, and understanding the effectiveness of mitigation translocations is critical given limited global conservation funding especially if the mitigation translocations undermine biodiversity conservation by failing to save individuals. We assessed the effectiveness of mitigation translocations by conducting a quantitative review of the global literature. A total of 59 mitigation translocations were reviewed for their adherence to the adaptive scientific approach expected of other conservation translocations and for the testing of management options to continue improving techniques for the future. We found that mitigation translocations have not achieved their potential as an effective applied science. Most translocations focused predominantly on population establishment‐ and persistence‐level questions, as is often seen in translocations more broadly, and less on metapopulation and ecosystem outcomes. Questions regarding the long‐term impacts to the recipient ecosystem (12% of articles) and the carrying capacity of translocation sites (24% of articles) were addressed least often, despite these factors being more likely to influence ultimate success. Less than half (47%) of studies included comparison of different management techniques to facilitate practitioners selecting the most effective management actions for the future. To align mitigation translocations with the relative success of other conservation translocations, it is critical that future mitigation translocations conform to an established experimental approach to improve their effectiveness. Effective mitigation translocations will require significantly greater investment of time, expertise, and resources in the future.

Invasive Asian Fusarium – Euwallacea ambrosia beetle mutualists pose a serious threat to forests, urban landscapes and the avocado industry - Kerry O’Donnell; Ran Libeskind-Hadas; Jiri Hulcr; Craig Bateman; Matthew T. Kasson; Randy C. Ploetz; Joshua L. Konkol; Jill N. Ploetz; Daniel Carrillo; Alina Campbell; Rita E. Duncan; Pradeepa N. H. Liyanage; et al. (Phytoparasitica, 2016)

Prevalence and anatomic site of Crassicauda sp. infection, and its use in species identification, in kogiid whales from the mid‐Atlantic United States - Tiffany F. Keenan‐Bateman; William A. McLellan; Craig A. Harms; Marina A. Piscitelli; Susan G. Barco; Victoria G. Thayer; Gretchen N. Lovewell; Karen L. Clark; Paul K. Doshkov; David S. Rotstein; Charles W. Potter; D. Ann Pabst (Marine Mammal Science, 2016)
The parasitic nematode Crassicauda sp. was initially described in kogiid whales from specimens collected within cervical tissues, uncommon sites of infection for this parasite. Crassicauda sp. has only been reported in Kogia breviceps to date, but no study has yet investigated a large sample of both kogiid species. A 15 yr record of 104 kogiid strandings ( K. sima , n = 40; K. breviceps , n = 64) in North Carolina and Virginia, U.S.A. was used to determine the prevalence of Crassicauda sp. across species, within species across sex, and within sex across length and life history categories. Crassicauda sp. was confirmed to be a species‐specific parasite among kogiids infecting only K. breviceps (prevalence = 45%). Within K. breviceps , prevalence was similar (45%) in both immature and mature males, but increased from 10% in immature to 76% in mature females. This study confirmed the cervico‐thoracic distribution of the parasite, and identified a novel site of infection in a previously undescribed exocrine gland associated with the pigmented “false gill slit.” The species‐specific nature of Crassicauda sp. infection, the exocrine gland, and the distinct features of the false gill slit pigmentation associated with the gland, are all useful characters to identify kogiid species in the field.

Fungal symbionts in three exotic ambrosia beetles, Xylosandrus amputatus, Xyleborinus andrewesi, and Dryoxylon onoharaense (Coleoptera: Curculionidae: Scolytinae: Xyleborini) in Florida - Craig Bateman; Paul E. Kendra; Robert Rabaglia; Jiri Hulcr (Symbiosis, 2015)

Inbreeding and inbreeding depression of early life traits in a cooperative mammal - JOHANNA F. NIELSEN; SINEAD ENGLISH; WILL P. GOODALL‐COPESTAKE; JINLIANG WANG; CRAIG A. WALLING; ANDREW W. BATEMAN; TOM P. FLOWER; ROBERT L. SUTCLIFFE; JAMIE SAMSON; NATHAN K. THAVARAJAH; LOESKE E. B. KRUUK; TIM H. CLUTTON‐BROCK; et al. (Molecular Ecology, 2012)
Mating between relatives often results in negative fitness consequences or inbreeding depression. However, the expression of inbreeding in populations of wild cooperative mammals and the effects of environmental, maternal and social factors on inbreeding depression in these systems are currently not well understood. This study uses pedigree‐based inbreeding coefficients from a long‐term study of meerkats ( Suricata suricatta ) in South Africa to reveal that 44% of the population have detectably non‐zero ( F > 0) inbreeding coefficients. 15% of these inbred individuals were the result of moderate inbreeding ( F ≥ 0.125), although such inbreeding events almost solely occurred when mating individuals had no prior experience of each other. Inbreeding depression was evident for a range of traits: pup mass at emergence from the natal burrow, hind‐foot length, growth until independence and juvenile survival. However, we found no evidence of significant inbreeding depression for skull and forearm length or for pup survival. This research provides a rare investigation into inbreeding in a cooperative mammal, revealing high levels of inbreeding, considerable negative consequences and complex interactions with the social environment.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)